Sustainable Tourism Leadership: A Collaborative Approach to Drive Ecosystem and Accelerate Innovation in Indonesia - Teguh Akbari, Taufan; Paras Ayu, Jati; Raif Khadijah, Siti Adelita; Reevany Bustami, Mohammad (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2025)
Tourism is a key contributor to Indonesia's GDP. Although the sector experienced major setbacks during the pandemic, it has since shown signs of recovery with notable achievements. One of the critical success factors involved in such a rebound is leadership. At the same time, the pandemic highlighted the importance of building a more sustainable tourism climate. While existing frameworks to create sustainable tourism mainly focus on technical and governance aspects, less attention has been given to the role of leadership. This research, therefore, examines how leadership enhances sustainable tourism in Indonesia. This study uses a qualitative approach to dig deeper into the perspectives of tourism industry players, from the government, NGOs, academics, and local communities, using Focus Group Discussion (FGD) coupled with a literature review. The findings show that various challenges in sustainable tourism leadership hinder its maximum growth. While innovation has become at the forefront of sustainable tourism stakeholders in Indonesia, it is still isolated from a bigger sustainable tourism ecosystem. Leadership frameworks should enhance, accelerate innovation, and spur ecosystem creation. This research provides a theoretical contribution to leadership literature, particularly the role of sustainable tourism leaders in improving the sustainable tourism climate. Practically, this research informs leaders in implementing their blueprint to create a robust, sustainable tourism industry.